Extracellular adenosine reversibly inhibits the activation of human regulatory T cells and negatively influences the achievement of the operational tolerance in liver transplantation. Issue 1 (31st August 2018) - Baroja‐Mazo, Alberto; Revilla‐Nuin, Beatriz; de Bejar, África; Martínez‐Alarcón, Laura; Herrero, José I.; El‐Tayeb, Ali; Müller, Christa E.; Aparicio, Pedro; Pelegrín, Pablo; Pons, José A.
Abstract : The artificial induction of tolerance in transplantation is gaining strength. In mice, a differential role of extracellular adenosine (eADO) for regulatory and effector T cells (Tregs and Teffs, respectively) has been proposed: inhibiting Teffs and inducing Tregs. The aim of this study was to analyze the action of extracellular nucleotides in human T cells and, moreover, to examine the influence of CD39 and CD73 ectonucleotidases and subsequent adenosine signaling through adenosine 2 receptor (A2 R) in the induction of clinical tolerance after liver transplant. The action of extracellular nucleotides in human T cells was analyzed by in vitro experiments with isolated T cells. Additionally, 17 liver transplant patients were enrolled in an immunosuppression withdrawal trial, and the differences in the CD39‐CD73‐A2 R axis were compared between tolerant and nontolerant patients. In contrast to the mice, the activation of human Tregs was inhibited similarly to Teffs in the presence of eADO. Moreover, the expression of the enzyme responsible for the degradation of ADO, adenosine deaminase, was higher in tolerant patients with respect to the nontolerant group along the immunosuppression withdrawal. Our data support the idea that eADO signaling and its degradation may play a role in the complex system of regulation of liver transplant tolerance. Abstract : Extracellular adenosine reversibly inhibits the activation of human regulatory T cells and negatively influences the achievement of operational tolerance in liver transplantation.